2021
DOI: 10.1017/ice.2021.148
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired infections among adult patients admitted for coronavirus disease 2019 (COVID-19)

Abstract: In a multicenter cohort of 963 adults hospitalized due to COVID-19, 5% had a proven hospital-acquired infection (HAI) and 21% had a proven/probable or possible HAI. Risk factors for proven/probable HAIs included intensive care unit admission, dexamethasone use, severe COVID-19, heart failure and antibiotic exposure upon admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 8 publications
3
15
1
Order By: Relevance
“…Patients with infectious complications in our study had worse outcomes, higher rates of acute respiratory distress syndrome, ICU admission, and increased mortality. These findings are consistent with those of previous reports of oncology patients with respiratory viral infections [4,6,7,9]. However, there are several variables that may influence the outcomes of cancer patients with COVID-19, particularly the presence of uncontrolled underlying malignancy.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Patients with infectious complications in our study had worse outcomes, higher rates of acute respiratory distress syndrome, ICU admission, and increased mortality. These findings are consistent with those of previous reports of oncology patients with respiratory viral infections [4,6,7,9]. However, there are several variables that may influence the outcomes of cancer patients with COVID-19, particularly the presence of uncontrolled underlying malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…In our large multinational cohort of onco-hematological patients with COVID-19, we found that the rate of co-infections at the time of diagnosis was more than double the rate reported in the general population [2][3][4][5] but the rate of superinfections was comparable to those observed in previous reports in the general population [6][7][8][9].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations